(untitled) (DIWANGKARA: Jurnal Pendidikan Bahasa, Sastra dan Budaya Jawa, 2023)
The study aimed at discussing cultural hegemony in the film Sang Penari. The film was adapted from novel Ronggeng Dukuh Paruk by Ahmad Thohari. This research used descriptive analysis. The researcher took the data and explained it based on the actual facts. The material object of this research focused on a film entitled Sang Penari, and the formal object of this research concentrated on cultural hegemony in the film Sang Penari based on Gramsci’s hegemonic study perspective. The results of the study showed that there were hegemonies in the culture of the local community: Javanese cultural hegemony and also modern cultural hegemony. It was represented through the characters in the film.